Communicating climate change in the Pacific using a bottom-up approach - Usha Sundar Harris (Asia Pacific Network, 2014)
While scientific evidence in support of climate change is growing, awareness and education about its effects, especially among vulnerable communities, is lacking, due to language and cultural barriers. Communities are unlikely to respond to government policies promoting mitigation and adaptation strategies without an improved perception of climate change risk at a local level. Mapping the flow of information between decision makers and citizens is an important part of this process. This article broadly explores the communication channels that are being used for awareness and knowledge sharing in the Pacific. At its core, the article discusses a way in which participatory media has been piloted to enable community discussion about issues around climate change in the Pacific Islands. The ‘bottom-up’ approach encourages participation of marginalised groups such as women, youth, and people with disabilities who bring diverse perspectives in content creation. This discursive space enables citizens to share knowledge and acquire better understanding of the impacts on livelihood and culture. However, a strong community network and consistent mentoring support are prerequisites for participatory media to have long term benefits.